The Role of Teachers' Effective Communication in Increasing Students' Learning Motivation in High School - Dina Noor Agustina; Babang Robandi; Rusdiono Muryanto (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
Education plays a key role in building a strong foundation for individual and societal development, with the level of education at senior secondary school (SMA) playing an important role in preparing students with the knowledge and skills necessary for their future. This journal article aims to investigate the role of effective teacher communication in increasing students' learning motivation in high school, using a literature review method to identify, evaluate, and synthesize related literature. The research results show that effective communication between teachers and students has a significant impact on their learning motivation. Factors such as the ability to listen with empathy and the use of effective teaching strategies have proven important in creating a motivating learning environment. This research emphasizes the importance of effective teacher communication in increasing students' learning motivation and offers practical guidelines for teachers to optimize their communication in the context of high school education. Taking into account these findings, this research provides a valuable contribution for educators, teachers and educational practitioners in efforts to improve quality learning at the high school level. Through implementing effective communication strategies, teachers can strengthen students' learning motivation, build positive relationships, and create a learning environment that is conducive to students' development.